Cost-Effectiveness Analysis of the Combination of Metformin-Insulin Glargine and Metformin-Glimepiride in Type 2 Diabetes Mellitus Patients in Rupit Hospital - Najmiatul Fitria; Leliani Fitri Anggraini; Yelly Oktavia Sari (Journal of Health Economic and Policy Research (JHEPR), 2023)
Type 2 diabetes mellitus (T2DM) is a chronic disease requiring lifelong care and much money. A combination of antidiabetic drugs aims to increase effectiveness in lowering blood sugar levels. The combination of two drugs consists of a first-line drug class plus another class of drugs with a different mechanism of action. This study aimed to determine the cost-effectiveness of the combination therapy of metformin-insulin glargine and metformin-glimepiride, expressed by the value of the Cost Effectiveness Incremental Ratio (ICER). Method: This research was a descriptive study, and data collection was carried out retrospectively using patient medical record data. This study used a healthcare provider perspective. Of the 406 population, only 102 samples met the inclusion criteria. Result: Fifty-seven records (55.88%) used the metformin-glimepiride combination, and the other forty-five (44.12%) used metformin-insulin glargine. The ICER value of random blood sugar during (RBG) was IDR 21,748.89 for every 1 mg/dL decrease in RBG. The ICER value of fasting blood sugar (FBG) was IDR 38,824.46 for every 1 mg/dL decrease in FBG. Meanwhile, the ICER of HbA1c value was IDR 43,257.46 for every 1% decrease in HbA1c. Conclusion: The three ICER values were in the northeast quadrant (quadrant I), where the metformin-insulin glargine therapy group had the better blood sugar value. Still, the costs required were also higher than the metformin-glimepiride group.